Nor Faridah’s wanderings as female flâneur in The Art of Naming - Mohd Fadhli Shah Khaidzir; Ruzy Suliza Hashim; Noraini Md. Yusof (Penerbit Universiti Kebangsaan Malaysia, 2021)
Travellers’ enthusiasm can drive them to explore new locations, especially those that are unknown and foreign to their eyes. Nor Faridah Abdul Manaf's anthology of poetry, The Art of Naming (2006) reflects the people and locations that played a significant role in crafting her poems. Using the role of a flâneur, which is closely related to the theory of psychogeography, we investigate how Nor Faridah, as a flâneuse (a female flâneur), wanders and strolls through the places she reconnoiters, and how her mental and behavioural aspects as a human being are affected by her environment. Her poems depict a strong perception, involvement, and representation of images focused on the immediate encounter of the urban cities visited, which serve as valuable pieces of evidence flâneurs while walking. Based on the analysis, the different places visited by the poet exhibit her values of humanity including empathy, generosity and love. Thus, Nor Faridah’s works illuminate the position of flâneur and flâneuse, demonstrating how spaces, contrary to what is thought to be pointless roaming, actually offer insights into understanding relationship between people and their locations. As a consequence, space and position are dialectically organised in human environmental history, since her sense of space is related to the locations she inhabits, which derive meaning from their spatial significance.